Theory and Practice in Implementing the Project for Strengthening the Profile of Pancasila Students in Madrasas as a Learning Recovery Effort - Andarusni Alfansyur; Saipul Annur; Yuniar (Didaktika: Jurnal Kependidikan, 2024)
This research is entitled Theory and Practice in Implementing the Project for Strengthening the Profile of Pancasila Students (P5) in Madrasas as a Learning Recovery Effort. This research aims to determine how implementing the Project for Strengthening the Profile of Pancasila Students relates to the learning recovery strategy and the supporting and inhibiting factors in implementing the project to strengthen the profile of Pancasila students regarding the learning recovery strategy. The theory used in this research is the theory put forward by George C. Edward III that four variables influence the successful implementation of a policy: 1. Communication; 2. Resources; 3. Disposition; and 4. Bureaucratic structure. With the case study method used, the results were obtained that: 1. Implementation of the Project for Strengthening the Pancasila Student Profile can be considered as a learning recovery effort.